2006
DOI: 10.1063/1.2199445
|View full text |Cite
|
Sign up to set email alerts
|

Negative differential resistance in dislocation-free GaN∕AlGaN double-barrier diodes grown on bulk GaN

Abstract: Double-barrier GaN resonant tunneling diodes with AlGaN barriers were fabricated on bulk (0001) single-crystal GaN substrates. Layers were grown using molecular-beam epitaxy with a rf plasma nitrogen source. Single diodes of 6μm diameter were prepared by inductively coupled plasma reactive ion etching. For many diodes clear negative differential resistance is observed around 2V with peak currents around 10kA∕cm2 and a peak-to-valley ratio of about 2 at room temperature. Its observation does not depend on speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 22 publications
5
78
1
Order By: Relevance
“…Therefore, this phenomenon seems to be more likely due to trapping effects than tunnelling transport. More recently, in 2006, Golka et al have reported an RTD structure fabricated on bulk GaN showing the same current-voltage behaviour, but they managed to partially recover the peak by annealing the samples at 350 °C, which confirms the hypothesis of trapping phenomenon [9]. In this work, we investigate the electronic transport through AlN/GaN/AlN double barrier structures, with different GaN quantum well thickness.…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, this phenomenon seems to be more likely due to trapping effects than tunnelling transport. More recently, in 2006, Golka et al have reported an RTD structure fabricated on bulk GaN showing the same current-voltage behaviour, but they managed to partially recover the peak by annealing the samples at 350 °C, which confirms the hypothesis of trapping phenomenon [9]. In this work, we investigate the electronic transport through AlN/GaN/AlN double barrier structures, with different GaN quantum well thickness.…”
Section: Introductionsupporting
confidence: 54%
“…The existence of defects such as charge traps and screw dislocations has led to the need for systematic verification of the origin of negative differential resistance (NDR) features. [13][14][15][16][17] Another important characteristic of AlGaN/GaN heterostructures is the large built-in electrostatic fields due to both spontaneous and piezoelectric polarization which alter the current-voltage (I-V) characteristics significantly. Recent advances in growth technology have reduced threading dislocation densities substantially to allow repeatable measurement of wurtzite and cubic AlGaN RTDs [18][19][20][21][22][23] and sequential tunneling devices.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a non-polar orientation should improve resonant tunneling when compared to a polar one, and that AlN barriers, compared to AlGaN ones, will result in higher peakto-valley ratios (Carnevale et al, 2012). This absence of reproducibility has been largely attributed to the charge trapping at dislocation sites (Golka et al, 2006). Furthermore, leakage paths through dislocations may lead to relatively small peak-to-valley ratios (1.03, Li et al), pushing the need for dislocation free nitride structures.…”
Section: Introductionmentioning
confidence: 99%